PENGEMBANGAN SISTEM PEMBELAJARAN BAHASA JEPANG BERBASIS ANDROID - Musfirah Putri Lukman; Hamdan Arfandy; Felicia Widjaja (SINTECH (Science and Information Technology) Journal, 2019)
In this study, the authors built a system for developing Japanese language learning based on Android. The expected benefits of this research are helping users to master Japanese. The method used in this study is the prototype method. The research begins by designing the Unified Modeling Language (UML) and Activity Diagrams. Then it is implemented into the Java Java programming language. Based on the results of the study, the author has succeeded in developing a Japanese language learning system at the elementary level to help elementary, middle and high school students and the Makassar community learn Japanese through the application. This application is designed to be easy to use for various ages. The results of this study were taken based on answers from 171 questionnaires conducted on students in the city of Makassar.